2019
DOI: 10.1007/s10554-019-01544-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age and cardiac disease on regional left and right ventricular myocardial motion in healthy controls and patients with repaired tetralogy of fallot

Abstract: Purpose-The assessment of both left (LV) and right ventricular (RV) motion is important to understand the impact of heart disease on cardiac function. The MRI technique of tissue phase mapping (TPM) allows for the quantification of regional biventricular three-directional myocardial velocities. The goal of this study was to establish normal LV and RV velocity parameters across a wide range of pediatric to adult ages and to investigate the feasibility of TPM for detecting impaired regional biventricular functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 63 publications
3
18
0
Order By: Relevance
“…TPM was acquired during breath‐holding and using a prospectively ECG gated, three‐directional velocity‐encoded, and black‐blood prepared gradient echo sequence as previously described . TPM images were obtained in the short‐axis orientation at the ventricular base, mid‐ventricle, and apex.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…TPM was acquired during breath‐holding and using a prospectively ECG gated, three‐directional velocity‐encoded, and black‐blood prepared gradient echo sequence as previously described . TPM images were obtained in the short‐axis orientation at the ventricular base, mid‐ventricle, and apex.…”
Section: Methodsmentioning
confidence: 99%
“…The workflow involved manual contouring (Fig. a) of the LV and RV epi‐ and endocardium across all three slices (base, mid, apex) and time frames for all controls and patients as described previously . After correcting for eddy currents, the acquired time‐resolved velocity data was transformed from Cartesian coordinates (v y , v x , v z ) to cylindrical coordinates in radial (v r ,), circumferential (v φ ), and long‐axis (v z ) motion components adapted to the motion components of the heart (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Velocities vx, vy, and vz were calculated as the phase difference of the velocity‐encoded data. Then, for both MB and SB PC data, the myocardial tissue motion of the left ventricle was analyzed using a custom MATLAB (MathWorks, Natick, MA) tool, 36 which allowed eddy current correction 37 and the manual segmentation of the myocardium. To provide a more representative view of the myocardial tissue motion, the in‐plane velocities vx and normalvnormaly were transformed into a polar coordinate system as previously described 30 .…”
Section: Methodsmentioning
confidence: 99%
“…Hu et al found that tissue tracking is feasible for assessing early ventricular dysfunction in patients post-Fontan with preserved ejection fraction [83]. Ruh et al demonstrated the feasibility of CMR tissue phase mapping to assess abnormal LV and RV motion ins tetralogy of Fallot patients [84]. Sugrue et al proposed using a time resolved MRA technique for assessing the pulmonary veins and left atrium in CHD patients [85].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%